Does Tax Evasion Affect Economic Crime? - Amedeo Argentiero; Bruno Chiarini; Elisabetta Marzano (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper examines the impact of tax evasion on criminal activities in Italy. Specifically, we consider three types of crime that are related to economic determinants: property crimes (including robbery, theft and car theft), fraud and usury. We estimate a dynamic panel using annual data from the Italian provinces (NUTS-3) for the 2006-2010 period and show that tax evasion positively affects economic crimes. Notably, the elasticity of tax evasion to fraud is related to the size of the tax burden; in addition, these crimes demonstrate different levels of persistence over time, reflecting different adjustment costs. Finally, we find that property crimes, fraud and usury are not influenced by deterrence or clearing-up variables.
Keywords: C33; H26; K42; 330; property crime; usury; fraud; tax evasion; deterrence effect